2019
DOI: 10.3847/2041-8213/ab53dd
|View full text |Cite
|
Sign up to set email alerts
|

EDGE: The Origin of Scatter in Ultra-faint Dwarf Stellar Masses and Surface Brightnesses

Abstract: We demonstrate how the least luminous galaxies in the universe, ultra-faint dwarf galaxies, are sensitive to their dynamical mass at the time of cosmic reionization. We select a low-mass (∼ 1.5 × 10 9 M ) dark matter halo from a cosmological volume, and perform zoom hydrodynamical simulations with multiple alternative histories using "genetically modified" initial conditions. Earlier-forming ultra-faints have higher stellar mass today, due to a longer period of star formation before their quenching by reioniza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 46 publications
8
88
0
Order By: Relevance
“…The stellar masses of the ultrafaint satellites are so small that they are beyond the reach of the current generation of cosmological hydrodynamical simulations, such as A (Sawala et al 2016;Fattahi et al 2016), A (Grand et al 2017) or F (Hopkins et al 2014(Hopkins et al , 2018, which, at best, have a stellar mass resolution of ★ ∼ 10 3 −10 4 M , although higher resolution may be achieved in simulations of isolated dwarf galaxies (e.g. Read et al 2016;Jeon et al 2017;Corlies et al 2018;Wheeler et al 2018;Munshi et al 2019;Rey et al 2019;Agertz et al 2020). Instead, we use the technique of semi-analytic galaxy modelling in which mass resolution is not an issue.…”
Section: Introductionmentioning
confidence: 99%
“…The stellar masses of the ultrafaint satellites are so small that they are beyond the reach of the current generation of cosmological hydrodynamical simulations, such as A (Sawala et al 2016;Fattahi et al 2016), A (Grand et al 2017) or F (Hopkins et al 2014(Hopkins et al , 2018, which, at best, have a stellar mass resolution of ★ ∼ 10 3 −10 4 M , although higher resolution may be achieved in simulations of isolated dwarf galaxies (e.g. Read et al 2016;Jeon et al 2017;Corlies et al 2018;Wheeler et al 2018;Munshi et al 2019;Rey et al 2019;Agertz et al 2020). Instead, we use the technique of semi-analytic galaxy modelling in which mass resolution is not an issue.…”
Section: Introductionmentioning
confidence: 99%
“…Using the genetic modification approach (Roth et al 2016;Rey & Pontzen 2018;Stopyra et al 2020), we can create alternative mass accretion histories for a galaxy. Rey et al (2019) modified one of the fiducial resolution EDGE dwarfs, Halo1459, such that it assembled later. They found that this leads to a larger, lower surface brightness, and lower metallicity dwarf -more similar to Eridanus II.…”
Section: Core Formation From Minor Mergersmentioning
confidence: 99%
“…They found that this leads to a larger, lower surface brightness, and lower metallicity dwarf -more similar to Eridanus II. As such, in this section, we resimulate the genetically modified later forming dwarfs from Rey et al (2019) at higher resolution to study how late formation impacts the central dark matter density.…”
Section: Core Formation From Minor Mergersmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible way to generate a zoom simulation is to calculate the entire cosmological volume at high resolution, then degrade the sampling outside the target region. This is inefficient, however, and entirely infeasible for some applications; for example, in the EDGE suite (Rey et al 2019a;Agertz et al 2020), the initial conditions resolution corresponds to an effective grid of 32768 3 . Storing a single such grid at double precision requires 32 terabytes; manipulating it is entirely out of reach.…”
Section: Zoom Initial Conditionsmentioning
confidence: 99%